Penerapan Teknik Self Management Untuk Membantu Penyesuaian Diri Bagi Orang Dengan HIV/AIDS (Odha) Di Yayasan Sriwijaya Plus Palembang - Azahara; Abdur Razzaq; Neni Noviza (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This study aims to determine the description of discipline in client "K" at Bunda Banyuasin Orphanage and the application of self management techniques to improve the discipline of client "K" at Bunda Banyuasin Orphanage. This research uses a qualitative field research approach and case study method. Data collection tools in this study are observation, interviews and documentation. Data analysis techniques in this study are pattern matchmaking, explanation, and time series analysis. The subjects of this research are client "K", client's friend "K" and Nursing Home Management. The description of client discipline "K" can be seen from 4 aspects, namely: the aspect of client rules "K" is a person who is less obedient in the rules that exist in the Orphanage. In the aspect of punishment client "K" often violates the rules and often gets a reprimand from the orphanage administrator. In the aspect of client appreciation "K" often also gets awards or praise from orphanage administrators. In the aspect of consistency client "K" can change and be consistent in improving discipline. The application of self management techniques on client "K" goes according to the steps of self management techniques. The results of the application of self management techniques on client "K" the first is the aspect of client "K" rules have begun to obey the rules in the orphanage. In the second aspect, namely client punishment "K" has not made mistakes and has begun to obey the orphanage administrators. The third aspect of appreciation is client "K" has started to do positive things so that he often gets awards. The fourth aspect is the consistency of client "K" has begun to change and consistently wants to be disciplined again in the future.